PENINGKATAN EFISIENSI DAN STABILITAS DYE SENSITIZED SOLAR CELL (DSSC) ORGANIK DENGAN ELEKTROLIT POLYETHYLENE GLYCOL - Trihutomo, Prihanto; Sholihin, Mohammad Riyadhu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This research will discuss the use of PEG with variations in molecular weight on the stability and efficiency of DSSC. Variations in the molecular weight of PEG used were 4000, 6000 and 10000 which were added to electrolytes containing iodine and potassium iodide using ethanol Pro Analyst as a solvent, then each electrolyte sample was tested for functional groups. Efficiency testing is carried out after the DSSC assembly is complete. Stability testing is carried out by repeated efficiency tests every 5 days after the first efficiency test and is carried out until the third test. The results of the FTIR functional group test showed that there were differences between the electrolyte samples without PEG and the electrolyte samples with PEG addition, but the PEG samples with different molecular weights showed identical functional group readings. The efficiency test results show that the use of PEG increases the efficiency of DSSC compared to DSSC without PEG where the DSSC sample with the lowest PEG molecular weight has the highest efficiency due to the low crystallinity of the polymeric material with low molecular weight thereby increasing ionic conductivity which affects the efficiency increase. The results of the stability test showed that the use of PEG could increase the stability of DSSC where the highest resistance was found in the DSSC with the lowest molecular weight PEG because of its low crystallinity which keeps its ionic conductivity high without being degraded so that efficiency can be maintained.